Stakeholder Analysis for Enhancing Ethics in Software Development: A Scoping Review - Marebane, Senyeki Milton; Mnkandla, Ernest (Journal of Information System and Informatics, 2025)
Stakeholder analysis has become a crucial means for achieving software development ethical goals. This scoping review study aims to provide an overview of the extent to which stakeholder analysis has been applied to enhance ethics in software development. The study explores research studies that have been published by IEEE, ACM, Science Direct, AIS and Journal of Business Ethics. PRISMA-ScR was employed to achieve the objective of the study. Only six research studies published from 1999 to 2015 met the selection criteria for data extraction and analysis. The results show that the focus of stakeholder analysis is on moral impulse, risk identification, stakeholder interactions, stakeholder classification and impact level. Furthermore, stakeholder analysis for enhancing ethics in software development is prevalent to empower the voiceless stakeholders, risk management and stakeholder mapping and quantification for measuring stakeholder impact on projects. The analysis of the results reveals several research gaps such as unavailable empirical studies beyond 2015, concentration only on requirements engineering and lack of studies on stakeholder analysis on emergent technologies. The implications of this study point to the need for more guidance and expanded use of stakeholder analysis across the complete software process to benefit software teams and ongoing research to harness the potential of this theory on enhancing ethics in the emergent technologies.